Estimation of radiative properties of thermal protective clothing. (5th May 2016) - Udayraj,; Talukdar, Prabal; Das, Apurba; Alagirusamy, Ramasamy
Highlights: Absorption and scattering coefficients of thermal protective fabrics are determined. Genetic algorithm is applied for the inverse estimation. Effects of pyrolysis of fabrics on radiative properties are analyzed. Radiative properties of different layers of protective clothing are determined. Abstract: Thermal protective clothing provides more safety and time to allow wearer to complete task or escape from external high heat or fire exposures. Radiation heat transfer is significant in such high temperature conditions. In the present work, radiative properties of various fabrics used for thermal protective clothing are estimated. Experimentally measured spectral directional–hemispherical reflectance and transmittance data available from literature are used to predict some of the radiative properties. A coupled finite volume radiative transfer equation solver along with genetic algorithm is used for this purpose. Radiative properties of some commonly used fabrics in thermal protective clothing at various heat source temperatures are predicted. Effects of pyrolysis on these properties are also analyzed. It is found that the extinction coefficient of the outermost layer of thermal protective clothing is very high as compared to the other inner layers, and it plays a significant role in blocking heat transfer to the skin. Scattering in fabrics used for thermal protective clothing is also found significant.